2000
DOI: 10.1063/1.372797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interface roughness on the exchange bias for NiFe/FeMn

Abstract: The effect of interface roughness on exchange bias for NiFe/FeMn bilayers is investigated for polycrystalline films and epitaxial films. Three different systems were investigated: polycrystalline Ta (10 nm)/Ni80Fe20 (10nm)/Fe50Mn50 (20 nm) films on oxygen plasma-etched Si(100) or Cu/H–Si(100) and epitaxial Ni80Fe20 (10nm)/Fe60Mn40 (20 nm) films on Cu/H–Si(110). For films grown on plasma-etched substrates, as the etching time is increased, film roughness increases up to 12 nm. For the polycrystalline films grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Despite several decades of intensive investigation there is still no complete consensus as to the origin of exchange bias [1,2], or the large body of phenomena that accompany the exchange-induced anisotropy, such as coercivity enhancement [1,2], training [1,2], and magnetization reversal asymmetry [4,5]. One issue that has been the subject of numerous investigations is that of the microstructure dependence of the exchange bias H E , particularly with regard to the AF layer [1,2,[6][7][8][9][10][11][12][13][14][15][16]. The interest in this issue arises because many exchange bias models predict a strong sensitivity to the existence of defects and disorder [6,[17][18][19][20][21], either at the AF/F interface or in the bulk of the AF layer.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several decades of intensive investigation there is still no complete consensus as to the origin of exchange bias [1,2], or the large body of phenomena that accompany the exchange-induced anisotropy, such as coercivity enhancement [1,2], training [1,2], and magnetization reversal asymmetry [4,5]. One issue that has been the subject of numerous investigations is that of the microstructure dependence of the exchange bias H E , particularly with regard to the AF layer [1,2,[6][7][8][9][10][11][12][13][14][15][16]. The interest in this issue arises because many exchange bias models predict a strong sensitivity to the existence of defects and disorder [6,[17][18][19][20][21], either at the AF/F interface or in the bulk of the AF layer.…”
Section: Introductionmentioning
confidence: 99%
“…For several systems, the H ex seems to be relatively insensitive to the roughness value [7,11], while in others the H ex varies in direct proportion to the roughness [9,10] or indicates an opposite variation [8]. Research has also shown that the relationship between the H ex and the roughness value is totally different for differently prepared samples [12].…”
Section: Introductionmentioning
confidence: 89%
“…The underlying mechanism and the role of the interface/ bulk structure have been investigated in a variety of EB systems [4][5][6][7][8][9][10][11][12] with different deposition techniques and F/AF materials. However, due to the wide variety of materials and deposition techniques used, the dependence of the EB field (H ex ) on the roughness is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…This difference in the EB parameters was attributed to distinct AF/FM spin configurations at the respective interfaces; however, the effect of the structural roughness was not taken into account [15,16]. Nevertheless, it has been reported [18] that the EB main parameters depend on several factors, such as: interfacial spin configuration, interface roughness between the FM and AF materials, textures (structural and magnetic), crystalline grain size and AF layer thickness. For example, Lee et al [17] have studied the NiFe (10 nm)/FeMn (30 nm)/NiFe (10 nm) trilayer by magnetization and transmission electron microscoNiFe (TEM) measurements and they have found that the seed and pinned layers have distinct H ex values due to different roughness values at the lower and upper NiFe/FeMn interfaces.…”
Section: Introductionmentioning
confidence: 90%